The Impact of Entrepreneurial Innovation on Real Estate Investment in Nigeria: A Smart PLS- SEM Approach - Saad, Abdulfatai; Milala, Sani Inusa (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
The real estate sector is undergoing significant changes due to the rise of innovative financing models and Prop-Tech adoption. However, the effects of these developments on key real estate variables such as financing options, investor confidence, market growth, and property valuation have not been adequately explored. This study addresses the gap by investigating how these factors interact and impact the overall real estate market, especially in the context of emerging economies. The need for this study arises from the growing reliance on technology and new financial structures in real estate, where understanding their implications is vital for ensuring market sustainability and investor security. The aim is to assess the influence of innovative financing models and Prop-Tech adoption on key real estate factors, with a focus on Nigerian real estate markets.  A structural equation modeling (SEM) approach was applied to data from 327 respondents in the real estate sector to test the relationships between these variables. Results indicate that innovative financing models have a significant positive impact on financing options (? = 0.606, p < 0.001), investor confidence (? = 1.108, p < 0.001), market growth (? = 0.182, p < 0.001), and property valuation (? = 0.173, p < 0.01). Similarly, Prop-Tech adoption positively affects market growth (? = 0.762, p < 0.001) and property valuation (? = 0.770, p < 0.001), but negatively influences investor confidence (? = -0.128, p < 0.001), suggesting that technology adoption can raise concerns among investors. In conclusion, the study highlights the significant roles of innovative financing models and Prop-Tech adoption in driving market growth and property valuation. However, their differing effects on investor confidence warrant attention, as addressing these concerns is essential for fostering balanced and sustainable growth in the real estate sector.